Quality Assessment of Organic Kefirs Made with Kefir Grains and Freeze-Dried Starter Cultures - Katarzyna Szkolnicka; Izabela Dmytrów; Anna Mituniewicz-Małek; Elżbieta Bogusławska-Wąs (Applied Sciences, 2024)
Organic dairy products, including fermented milk, are gaining popularity among consumers. Traditionally, for kefir production, kefir grains are used; however, in the modern industry, freeze-dried cultures are commonly employed. This study aimed to analyze the quality of kefirs produced from organic cow milk with two fermentation times (12 and 24 h) with the use of kefir grains or freeze-dried culture. During a 3-week storage period, physicochemical properties, color, syneresis index, texture, sensory, and microbiological quality were evaluated. The results proved that organic cow milk was suitable for kefir production both with the use of kefir grains and freeze-dried culture. Using freeze-dried culture and a 24 h fermentation period resulted in kefir with the lowest syneresis tendency (3.65–9.62%), along with the best textural properties (the highest cohesiveness and viscosity index), and desired sensory characteristics. Kefir grains had a better acidification ability, and the resulting products had a higher count of yeasts, lactobacilli, and lactococci compared with kefirs obtained with freeze-dried culture. However, both the type of starter culture and the fermentation time influenced the product’s quality. The longer fermentation time of 24 h was more appropriate for the kefir production. Kefir grains, as a traditional form of kefir culture, may be preferred in organic kefir production.